IbM BK teacher for SMA and its equivalent in Sidoarjo District - Eko Hardiansyah; Lely Ika Mariyati (Universitas Muhammadiyah Sidoarjo, 2016)
The role of guidance and counseling teachers is very strategic in school programs. Guidance and counseling activities have many important functions for the development of students in schools which ultimately lead to an increase in academic achievement and a decrease in student behavior problems. The goal of IbM BK teachers for high school and equivalent in Sidoarjo District is to improve the quality of BK teacher services. The first specific target is to increase the capacity of BK teachers in conducting individual group counseling using choice theory. The second is the provision of student development books so that BK teachers have a source of information to communicate student problems with parents, principals, subject teachers, and other parties such as psychologists or psychiatrists for sustainable treatment. The third is an increase in the network of cooperation between schools and the Sidoarjo Health Office regarding referral services in severe cases that are difficult for BK teachers to handle alone. The results obtained are 1) BK teachers have started using individual and group counseling in handling students on the basis of choice theory; 2) They have also begun to be able to use the principle of choice theory in interacting with other students and teachers so that students seem less tense when dealing with BK teachers; 3) By applying the principles of choice theory, BK teachers feel that the counseling carried out can be more directed, structured, and the impact of change is more visible on the students they treat; 4) BK teachers can conduct classroom action research (CAR) using the instruments provided in the student development book; 5) With the SOP for Transfer of Hands, teachers can have an idea of ​​the flow and parties who need to be invited to work together if they get students with severe psychological problems that are difficult to handle on their own, although currently they have not yet received such cases.